Nigeria Strategic Gas Plan - World Bank (Washington, DC, 2014)
The study underlines the government's strategic role in promoting proactive gas development schemes, and the drive for change in gas flaring reduction, for better use of Nigeria's gas resources. It is an analysis and integration of independent proposals from international oil companies to the Government of Nigeria for gas utilization projects. The elements and policy framework are evaluated, so as to formulate a consolidated development plan for the country's gas resources, through a series of viable projects. It covers the basic elements of gas supply, the uses for gas, the sequence involved in gas planning evaluations, the background issues for gas planning - for Nigeria, and the development of a Stage I Gas Management Model.